Research on the Green Consumption Development Based on Fuzzy Comprehensive Evaluation—A Case Study of the Middle and Lower Reaches of the Yangtze River - Li Tingting (SHS Web of Conferences)
Studying the development and influencing factors of green consumption plays a guiding role in building a strong country in China and achieving carbon neutrality. On this basis, this paper first constructs the first, second and third-level indicators of green consumption development with 15 third-level indicators. Then, the analytic hierarchy process (AHP) is used to assign weights to the indicators. Finally, the score of green consumption development in provinces and cities is measured and compared by the fuzzy comprehensive evaluation. As a result, it has the greatest impact on the operating income of high-tech enterprises and local fiscal environmental protection expenditure in Shanghai, Jiangsu, Anhui, Zhejiang, Hubei and Hunan provinces. Jiangsu Province has the best development, while Hunan Province has the worst one. Some suggestions are also put forward to strengthen residents’ awareness and enterprises’ innovative production.